ANALISIS PROKSIMAT PADA BRIKET BATUBARA NON KARBONISASI TERHADAP JENIS DAN KOMPOSISI PEREKAT TAPIOKA DAN PEREKAT SAGU - Vivi Widiawati; Agus Winarno; Tommy Trides; Windhu Nugroho; Henny Magdalena (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
The demand of the fuel oil in the world increasing with the rate population and industrial growth. The alternative solid fuel which is the main ingredient of that is coal, contains the high calorific value so that it can be replaced petroleum product and be used is briquette. In this study conducted proximate test on non-carbonized coal briquettes beetwen tapioca adhesive and Sago adhesive. In the study, the methods used approach issues of extracting research from established theories and data of observed objects. The analysis result of proximate test briquettes coal with tapioca adhesive on Balikpapan Formation, pulau balang Formation, kampung baru formation obtained the value of IM is 11,68% - 24,48 %, AC is 2,62 - 5,68 %, VM is 39,40 - 52,49 %, and FC is 12,95 - 46,32 %. whereas on coal briquettes with Sago adhesive on Balikpapan Formation, pulau balang Formation, kampung baru formation obtained the value IM is 13,11 - 30,57 % on, AC is 3,71 - 5,75 %, VM is 47,83 - 53,22 %, and FC is 10,47 - 41,34 %.